2020
DOI: 10.1038/s41371-020-00405-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between renin–angiotensin–aldosterone system inhibitor treatment, neutrophil–lymphocyte ratio, D-Dimer and clinical severity of COVID-19 in hospitalized patients: a multicenter, observational study

Abstract: The aim of this study was to investigate the possible relationship between worse clinical outcomes and the use of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) in hospitalized COVID-19 patients. A total of 247 adult patients (154 males, 93 females; mean age: 51.3 ± 14.2 years) hospitalized for COVID-19 as confirmed by polymerase chain reaction (PCR) were retrospectively reviewed. Demographic and clinical characteristics and laboratory parameters were analyzed using va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
9
0
2
Order By: Relevance
“…Similar results were observed in multiple small retrospective cohort studies. 29 , 36 , 42 , 54 It is worth noting that most studies included in the meta-analyses were retrospective and observational; with these study designs, unmeasured confounding factors and potential biases are inevitable. In addition, patients receiving ACEIs/ARBs are more likely to have heart failure, cardiovascular disease, hypertension, and comorbidities, which are associated with an increased risk of death among patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in multiple small retrospective cohort studies. 29 , 36 , 42 , 54 It is worth noting that most studies included in the meta-analyses were retrospective and observational; with these study designs, unmeasured confounding factors and potential biases are inevitable. In addition, patients receiving ACEIs/ARBs are more likely to have heart failure, cardiovascular disease, hypertension, and comorbidities, which are associated with an increased risk of death among patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In recent months, several clinical studies have reported that the use of ARBs and ACE-Inhs. does not affect disease progression and mortality rates in COVID-19 patients ( Anzola et al, 2020 ; Bae et al, 2020 ; Braude et al, 2020 ; Cordeanu et al, 2020 ; H. Cui et al, 2020 ; Di Castelnuovo et al, 2020 ; Gormez et al, 2020 ; Hippisley-Cox et al, 2020 ; Kalra et al, 2020 ; Khan et al, 2020 , Kim et al, 2020 ; Kocayigit et al, 2020 ; Lafaurie et al, 2020 ; J. Lee et al, 2020 ; Sardu et al, 2020 ; Soleimani et al, 2020 , Taher et al, 2020 ; Trifirò et al, 2020 , Wang et al, 2020 ). Altogether, these results indicate that the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 95%
“…For this systematic review, 58 cohort studies and three case-control studies were included, most of them conducted in China and 20 studies in other countries. On the other hand, our primary outcome (severity) was present in 36 studies, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] the secondary outcome (mortality)…”
Section: Studycharacteristicsmentioning
confidence: 99%